2015
DOI: 10.1111/cei.12453
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal brain injury and systemic inflammation: modulation by activated protein C ex vivo

Abstract: SummaryInfection and inflammation can be antecedents of neonatal encephalopathy (NE) and increase the risk of neurological sequelae. Activated protein C (APC) has anti-coagulant and anti-inflammatory effects and provides neuroprotection in brain and spinal cord injury. We examined neutrophil and monocyte responses to lipopolysaccharide (LPS) in infants with NE compared with healthy adult and neonatal controls, and also studied the effect of APC. Whole blood was incubated with LPS and APC and Toll-like receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 47 publications
(66 reference statements)
1
12
0
Order By: Relevance
“…Notably, 3K3A-APC administration at 1 h after resuscitation from intrapartum asphyxia also improved loss of body weight in the first 24 h after the hypoxic insult, which is likely to be secondary to reduced feeding and therefore reflects the general well-being of the newborn spiny mice. The amelioration of cell death by 3K3A-APC administration is consistent with previous studies of APC focused on neonatal brain injury [12,13].…”
Section: K3a-apc To Prevent Neuronal Apoptotic Cell Death Following supporting
confidence: 90%
See 1 more Smart Citation
“…Notably, 3K3A-APC administration at 1 h after resuscitation from intrapartum asphyxia also improved loss of body weight in the first 24 h after the hypoxic insult, which is likely to be secondary to reduced feeding and therefore reflects the general well-being of the newborn spiny mice. The amelioration of cell death by 3K3A-APC administration is consistent with previous studies of APC focused on neonatal brain injury [12,13].…”
Section: K3a-apc To Prevent Neuronal Apoptotic Cell Death Following supporting
confidence: 90%
“…APC has been shown to downregulate NFκB-driven inflammatory cytokine release from leukocytes and endothelial cells [7], downregulate pro-apoptotic proteins Bax and p53 [8], and protect the endothelial barrier [9][10][11]. Experimental studies examining the neuroprotective effects of APC in neonatal HIE have shown that APC treatment reduced the level of apoptosis in the dentate gyrus and cornu ammonis CA1, CA2, and CA3 hippocampal regions compared to the vehicle-treated group [12] and ameliorated systemic inflammation [13]. However, the anticoagulant properties of APC increase the risk of bleeding and intracranial hemorrhage in neonates, as shown in a subgroup of children < 60 days of age with sepsis who were treated with APC [14].…”
Section: Introductionmentioning
confidence: 99%
“…Our team and others uncovered that the upregulation of IL-1 plays a key role in chorioamnionitis, and in associated neonatal ischemic brain injuries ( 54 , 79 , 82 , 84 , 94 97 ). Our preclinical studies, and others, showed that prenatal IL-1 blockade using IL-1Ra is protective against chorioamnionitis, associated FIRS, and subsequent brain injuries ( 73 , 74 , 106 108 ).…”
Section: New Hypotheses Bringing New Treatmentsmentioning
confidence: 97%
“…For instance, Stridh et al showed in a newborn mouse model [at postnatal day (P) 9, i.e., a level of brain development equivalent to the term human newborn] of NAIS that TLR-2 deficiency protected the brain from infarcts ( 94 ). Energy failure due to hypoxia and inflammation combine their effects to increase the oxidative stress ( 96 , 97 ). Besides, LPS and other pathogen components interact with various TLR to increase the synthesis of a wide set of proinflammatory cytokines and chemokines (Figure 2 B) ( 54 , 73 , 74 , 95 ).…”
Section: Inflammatory Pathways Involved In Brain Ischemic Injuries Ofmentioning
confidence: 99%
“…The initial hypoxic insult leads to primary energy failure, necrosis, subsequent glutamate release, oxidative stress, and as a result excitotoxicity and widespread necrosis and necroptosis within the first 6 h of the insult [21][22][23]. Neural tissue damage could be aggravated by previous sensitization due to inflammation, which could lead to increased oxidative stress and an increased production of pro-inflammatory cytokines [19,[24][25][26][27][28]. The second phase of neuroinflammation occurs from 24 until 72 h after the initial HI insult and is characterized by the production of inflammatory cytokines, the migration of leukocytes into the brain tissue, and consequent apoptosis.…”
Section: Introductionmentioning
confidence: 99%